Arquivos privados e interesse público: caminhos da patrimonialização documental - Molina, Talita dos Santos (2013)
This dissertation examines how institutions and safeguard cultural heritage preservation deal documentary heritage, and particularly private files, discussing changes in formulations and current conceptions and actions relating to documentary heritage institutions. Therefore, we attempted to follow trajectories and actions in relation to documentary heritage in the heritage processes relating to private files submitted to IPHAN (Institute of National Historical and Artistic Heritage) and CONDEPHAAT (Council for the Protection of Historical, Archaeological and Tourism) in requests tipping and CONARQ (National Council of Archives) in requests "declaration of public and social interest." The final text is presented in three chapters. The first chapter discusses fundamental concepts and norms and legal instruments that articulate the actions of documentary heritage and private archives in the country. The second and third chapters, devoted to the discussion of the processes and tipping declaration of public interest and social concern, respectively, of shares related to personal files and archives institutional and social entities